Perturbations in nitric oxide homeostasis promote Arabidopsis disease susceptibility towards Phytophthora parasitica. (9th July 2021) - Cui, Beimi; Ma, Xiangren; Li, Yuan; Zhou, Yu; Ju, Xiuyun; Hussain, Adil; Umbreen, Saima; Yuan, Bo; Tabassum, Anika; Lubega, Jibril; Shan, Weixing; Loake, Gary J.; et al.
Abstract: Phytophthora species can infect hundreds of different plants, including many important crops, causing a number of agriculturally relevant diseases. A key feature of attempted pathogen infection is the rapid production of the redox active molecule nitric oxide (NO). However, the potential role(s) of NO in plant resistance against Phytophthora is relatively unexplored. Here we show that the level of NO accumulation is crucial for basal resistance in Arabidopsis against Phytophthora parasitica . Counterintuitively, both relatively low or relatively high NO accumulation leads to reduced resistance against P. parasitica . S ‐nitrosylation, the addition of a NO group to a protein cysteine thiol to form an S ‐nitrosothiol, is an important route for NO bioactivity and this process is regulated predominantly by S ‐nitrosoglutathione reductase 1 (GSNOR1). Loss‐of‐function mutations in GSNOR1 disable both salicylic acid accumulation and associated signalling, and also the production of reactive oxygen species, leading to susceptibility towards P. parasitica . Significantly, we also demonstrate that secreted proteins from P. parasitica can inhibit Arabidopsis GSNOR1 activity. Abstract : Perturbations in Arabidopsis nitric oxide homeostasis promote disease susceptibility towards the oomycete pathogen Phytophthora parasitica .